2020
DOI: 10.1186/s12960-020-00488-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable workforce: South African Audiologists and Speech Therapists

Abstract: Background: Audiologists and Speech Therapists play a vital role in addressing sustainable development goals by supporting people who are marginalised due to communication challenges. The global burden of disease and poor social living conditions impact negatively on the development of healthy communication, therefore requiring the services of Audiologist and Speech therapists. Against this background, we examined the demographic profile and the supply, need and shortfall of Audiologists and Speech Therapists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(123 citation statements)
references
References 14 publications
2
90
1
Order By: Relevance
“…Most respondents were from Gauteng (n = 16), followed by Western Cape (n = 11), with 23 SLPs from the public sector, and 16 working in the private health sector, namely, 13 working in a private hospital and three SLPs working in a private rehabilitation context. It was unfortunate that the response rate was not higher, given that there are currently 2643 SLPs registered with the HPCSA (Pillay et al, 2020). Whilst acknowledged under the limitations, the researchers were cognisant of the timing of data collection -there were an unusually high number of surveys being completed at the time of the data collection because of the coronavirus pandemic.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most respondents were from Gauteng (n = 16), followed by Western Cape (n = 11), with 23 SLPs from the public sector, and 16 working in the private health sector, namely, 13 working in a private hospital and three SLPs working in a private rehabilitation context. It was unfortunate that the response rate was not higher, given that there are currently 2643 SLPs registered with the HPCSA (Pillay et al, 2020). Whilst acknowledged under the limitations, the researchers were cognisant of the timing of data collection -there were an unusually high number of surveys being completed at the time of the data collection because of the coronavirus pandemic.…”
Section: Participantsmentioning
confidence: 99%
“…http://www.sajcd.org.za Open Access with regard to who accesses these services and the availability of resources (Pillay, Tiwari, Kathard, & Chikte, 2020;Shai & Ogunnubi, 2018). Thus, it was important to understand how healthcare professionals in both private and public, who are working in low-and middle-income countries such as SA, experienced the impact of COVID-19 at the strictest levels of lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…Speech and language therapy services are sparse in these countries. For example, in Sub-Saharan Africa, there was a ratio of 0-6 speech and language therapists per million population (Jochmann 2006, Mulwafu et al 2017, Wylie et al 2012 and similar limitations can be found in Asia and other parts of Africa (Cheng 2010, Chu et al 2019, Haas 2015, Pillay et al 2020. Many of the Sub-Saharan African countries have no training programmes for SLTs (Mulwafu et al 2017).…”
Section: Social Inequalities In the Receipt Of Health And Social Carementioning
confidence: 96%
“…2019, Haas 2015, Pillay et al . 2020). Many of the Sub‐Saharan African countries have no training programmes for SLTs (Mulwafu et al .…”
Section: Social Inequalities In the Receipt Of Health And Social Carementioning
confidence: 99%
“…Consequently, human resource analysis shows higher disability prevalence and higher service demands in contexts with shortages of human resources (11). While many human resource national plans and reviews tend to leave out rehabilitation (2), studies in countries like in South Africa (17)(18)(19), in Malawi (20) and in Kenya, Tanzania and Uganda (9,21) indicate this field and its workforce constraints in less resourced settings (22).…”
Section: Introductionmentioning
confidence: 99%